Strategic Orientation as Booster of Small Business Innovation: is it Possible? - Mulyono, Kemal Budi; Susilaningsih; Hindrayani , Aniek; Totalia , Salman Alfarisy; Rahman, M. Fathur (Jurnal Dinamika Manajemen, 2024)
This study investigates the role of market orientation, entrepreneurial orientation, and learning orientation as boosters of the impact of knowledge management on innovation. This study filling the gap of inconsistent relation among knowledge management on business innovation in small business context. This research analyzed a quantitative design using a survey method and SEM-PLS modeling. Questionnaires were distributed to 160 respondents, who were small business owners, using the inverse root square sample size method with purposive sampling. The data were analyzed using the SEM-Warp PLS method. The research results indicate that market orientation, entrepreneurial orientation, and learning orientation significantly mediate the relationship between knowledge management and business innovation. These findings suggest that small entrepreneurs need to allocate time to enhance these three orientations through activities such as knowledge exploration, creation, and dissemination through entrepreneurial associations or business seminars or workshops, by doing so, they can promote increased innovation and improve their competitive advantage in the market.